SEDIMENT AND COASTLINE CHANGE ANALYSIS OF MESKOM VILLAGE, RIAU - Rachmani, Chairunisa; Ghalib, Musrifin; ', Rifardi (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2017)
The main purpose of study is to find out characteristics of sediment and velocity of costline change in Meskom Village which is located off the Bengkalis district, Riau. Sediment samples collacted at 5 stations in coastal area of Meskom Village in November 2015 by the survey method. Station 1 and 2 in south of Meskom Village which is sedimentation area. Station 3, 4 and 5 in north of Meskom Village which is abrasion area. Coastline change analysis used image data by Landsat 5 TM (1995 and 2005) and Landsat 8 LDCM (2015) which processed by Quantum GIS 2.13.4.Meskom Village has characteristic of sediment medium silt in the south coastal area and very fine sand in the north coastal area. The results of sediment analysis mentioned above, skewness value indicated that abrasion and sedimentasion influenced of current and wave. Sorting value indicated that the sediment coastal of Meskom Village has unstable environmentally. Interpretation of image data mentioned that the most coastal increase (sedimentasion) at station 2, that is 29,77 meter/year seen from 1995 to 2015. While the most coastal decrease (abrasion) at station 4, that is 38,02 meter/year.Based on the result mentioned above, sediment characteristic able to explained influences the environment condition causes coastline changing in the some area.Keywords: Sediment, Coastline change, Abrasion, Remote Sensing